The performance of the National Early Warning Score and National Early Warning Score 2 in hospitalised patients infected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). (February 2021) - Kostakis, Ina; Smith, Gary B.; Prytherch, David; Meredith, Paul; Price, Connor; Chauhan, Anoop; ,; Chauhan, Anoop; Meredith, Paul; Mortlock, Alice; Schmidt, Paul; Spice, Claire; et al.
Abstract: Introduction: Since the introduction of the UK's National Early Warning Score (NEWS) and its modification, NEWS2, coronavirus disease 2019 (COVID-19), has caused a worldwide pandemic. NEWS and NEWS2 have good predictive abilities in patients with other infections and sepsis, however there is little evidence of their performance in COVID-19. Methods: Using receiver-operating characteristics analyses, we used the area under the receiver operating characteristic (AUROC) curve to evaluate the performance of NEWS or NEWS2 to discriminate the combined outcome of either death or intensive care unit (ICU) admission within 24 h of a vital sign set in five cohorts (COVID-19 POSITIVE, n = 405; COVID-19 NOT DETECTED, n = 1716; COVID-19 NOT TESTED, n = 2686; CONTROL 2018, n = 6273; CONTROL 2019, n = 6523). Results: The AUROC values for NEWS or NEWS2 for the combined outcome were: COVID-19 POSITIVE, 0.882 (0.868−0.895); COVID-19 NOT DETECTED, 0.875 (0.861−0.89); COVID-19 NOT TESTED, 0.876 (0.85−0.902); CONTROL 2018, 0.894 (0.884−0.904); CONTROL 2019, 0.842 (0.829−0.855). Conclusions: The finding that NEWS or NEWS2 performance was good and similar in all five cohorts (range = 0.842−0.894) suggests that amendments to NEWS or NEWS2, such as the addition of new covariates or the need to change the weighting of existing parameters, are unnecessary when evaluating patients with COVID-19. Our results support the national and international recommendations for the use of NEWS or NEWS2 for the assessment of acute-illness severity in patients with COVID-19.